A novel long-tailed myovirus represents a new T4-like cyanophage cluster - Liu, Yuanfang; Meng, Xue; Zheng, Hongrui; Cai, Lanlan; Wei, Shuzhen; He, Minglu; He, Jiale; Hao, Yue; Ge, Chang; Liu, Jihua; Chen, Feng; Xu, Yongle (Frontiers in Microbiology, 2023)
Cyanophages affect the abundance, diversity, metabolism, and evolution of picocyanobacteria in marine ecosystems. Here we report an estuarine Synechococcus phage, S-CREM2, which represents a novel viral genus and leads to the establishment of a new T4-like cyanophage clade named cluster C. S-CREM2 possesses the longest tail (~418 nm) among isolated cyanomyoviruses and encodes six tailrelated proteins that are exclusively homologous to those predicted in the cluster C cyanophages. Furthermore, S-CREM2 may carry three regulatory proteins in the virion, which may play a crucial role in optimizing the host intracellular environment for viral replication at the initial stage of infection. The cluster C cyanophages lack auxiliary metabolic genes (AMGs) that are commonly found in cyanophages of the T4-like clusters A and B and encode unique AMGs like an S-type phycobilin lyase gene. A variation in the composition of tRNA and cis-regulatory RNA genes was observed between the marine and freshwater phage strains in cluster C, reflecting their different modes of coping with hosts and habitats. The cluster C cyanophages are widespread in estuarine and coastal regions and exhibit equivalent or even higher relative abundance compared to those of clusters A and B cyanophages in certain estuarine regions. The isolation of cyanophage S-CREM2 provides new insights into the phage-host interactions mediated by both newly discovered AMGs and virionassociated proteins and emphasizes the ecological significance of cluster C cyanophages in estuarine environments.